Understanding the Impact of Medicaid-Serving Primary Care Team Functioning and Clinical Context on Cancer Care Treatment Quality: Implications for Addressing Structural Inequities. Issue 1 (6th December 2022) - O'Malley, Denalee M.; Doose, Michelle; Howard, Jenna; Cantor, Joel C.; Crabtree, Benjamin F.; Tsui, Jennifer
Abstract : PURPOSE: Primary care factors related to Medicaid enrollees' receipt of guideline concordant cancer treatment is understudied; however, team structure and processes likely affect care disparities. We explore Medicaid-serving primary care teams functioning within multiteam systems to understand performance variations in quality of breast and colorectal cancer care. METHODS: We conducted a comparative case study, using critical case sampling of primary care clinics in New Jersey, to provide maximum variation on clinic-level care performance rates (Medicaid enrollees' receipt of guideline-concordant treatment). Site evaluations, conducted from 2019 to 2020, included observation (2-3 days) and interviews. Using a multistep analytic process, we explored contextual factors within primary care that may contribute to cancer care performance variations. RESULTS: We identified performance variations stemming from adaptations of multiteam system inputs and processes on the basis of contextual factors (ie, business model, clinic culture). Team 1 (average performer), part of a multisite safety-net clinic system, mainly teamed outside their organization, relying on designated roles, protocol-based care, and quality improvement informed by within-team metrics. Team 2 (high performer), part of a for-profit health system, remained mission-driven to improve urban health, teamed exclusively with internal teams through electronically enabled information exchange and health system–wide quality improvement efforts. Team 3 (low performer), a physician-owned private practice with minimal teaming, accepted Medicaid enrollees to diversify their payer mix and relied on referral-based care with limited consideration of social barriers. CONCLUSION: Primary care team structures and processes variations may (in part) explain performance variations. Future research aiming to improve care quality for Medicaid populations should consider primary care teams' capacity and context in relation to composite teams to support care quality improvements in subsequent prospective trials.